Gebremicheal's story - International Livestock Research Institute (International Livestock Research Institute, 2012)
This photofilm tells the story of Gebremicheal Desta, a farmer in Ethiopia's Tigray region who benefited from the ILRI-led Improving Productivity and Market Success of Ethiopian Farmers (IPMS) project. Recorded in 2010, it highlights some of the results of the project, which worked closely with Ethiopia's Ministry for Agriculture and Rural Development to improve farmers' livelihoods.